Efficacy of endoscopic ligation with O-ring closure for prevention of bleeding after gastric endoscopic submucosal dissection under antithrombotic therapy: a prospective observational study - Nishiyama, Noriko; Kobara, Hideki; Kobayashi, Nobuya; Chiyo, Taiga; Tada, Naoya; Kozuka, Kazuhiro; Matsui, Takanori; Yachida, Tatsuo; Fujihara, Shintaro; Shi, Tingting; Masaki, Tsutomu (Endoscopy, 2022)
Background We examined the efficacy of a novel endoscopic ligation technique with O-ring closure (E-LOC) to prevent bleeding after gastric endoscopic submucosal dissection (ESD) under antithrombotic therapy.Methods This single-center prospective study involved consecutive patients who were taking antithrombotic agents and underwent gastric ESD. E-LOC was performed by anchoring the nylon loop with hemoclips on both defect edges and/or the exposed muscle layer, and using O-ring band ligation around these deployed clips. The primary outcome was post-ESD bleeding rate. Secondary outcomes were complete closure rate, procedure time, sustained closure rate, and complications.Results 48 patients were finally analyzed. The post-ESD bleeding rate was 0 %, the complete closure rate was 97.9 %, and the mean closure time was 29.9 minutes. The sustained closure rate was 95.8 % at postoperative day 2–3 and 33.3 % at postoperative day 10–11. No complications occurred.Conclusion E-LOC may be an effective option for closing mucosal defects after gastric ESD under antithrombotic therapy. However, the preventive effect on post-ESD bleeding should be further investigated in high risk groups.